Endoscopic ultrasound-guided gastroenterostomy using novel tools designed for transluminal therapy: a porcine study - Binmoeller, K. F.; Shah, J. N. (Endoscopy, 2012)
Background and study aims: Surgical gastroenterostomy is associated with appreciable morbidity and mortality. We evaluated the technical feasibility and outcomes of a new method of endoscopic ultrasound (EUS)-guided gastroenterostomy using novel tools designed for transluminal therapy.Methods: In one acute and four survival female pigs, a gastroenterostomy was created under EUS guidance. Novel tools used included: (i) an anchor wire; (ii) an access device; (iii) a fully covered metal stent with bilateral lumen-apposing anchors. The anchor guide wire was inserted through a standard 19-G fine needle aspiration (FNA) needle to appose the small-bowel and stomach walls. The access device created a 3.5-mm fistula opening for insertion of the stent delivery catheter. The stent lumen was dilated to 10 mm to pass a gastroscope into the small bowel. Results: The procedure was technically successful in all animals. No bleeding occurred. In one acute animal, necropsy showed good stent position and no tissue injury. In four survival animals, the stents remained fully patent and all animals showed normal eating behavior without signs of infection. Stents were easily removed without tissue trauma at 4.5 weeks (n = 3) or 5.5 weeks (n = 1). After stent removal, the tracts appeared mature and were easily intubated with the gastroscope. Necropsy and histopathology showed complete fusion of the stomach and small-bowel wall layers at the site of gastroenterostomy. Conclusions: EUS-guided gastroenterostomy is feasible using novel tools with no adverse outcomes in a survival porcine model. Further study of this is indicated as an alternative to surgical bypass for the palliation of malignant gastric outlet obstruction in appropriately selected patients.